Heat treatment of gears a practical guide for engineers - Rakhit, A. K. (ASM International, 2000)
Annotation Rakhit wants other engineers to avoid the considerable trouble he had understanding the art of gear heat treatment when he first embarked on a career in gear design and manufacturing. He explains how heat treating and gears made of some kinds of steel gives the gears high geometric accuracy, but can also distort them and raise the cost of manufacturing, so a gear engineer needs to excel in manufacturing, lubrication, life and failure analysis, and machine design as well as design. He presents a case history of each successful gear heat treatment process that provide information on the quality of gear that can be expected with the proper control of material and processes. Annotation copyrighted by Book News Inc., Portland, OR